Mechanisms of Pulmonary Hypertension in Acute Respiratory Distress Syndrome (ARDS) - Revercomb, Lucy; Hanmandlu, Ankit; Wareing, Nancy; Akkanti, Bindu; Karmouty-Quintana, Harry (Frontiers in Molecular Biosciences, 2021)
Background: Acute Respiratory Distress Syndrome (ARDS) is a severe and often fatal disease. The causes that lead to ARDS are multiple and include inhalation of salt water, smoke particles, or as a result of damage caused by respiratory viruses. ARDS can also arise due to systemic complications such as blood transfusions, sepsis or pancreatitis. Unfortunately, despite a high mortality rate of 40%, there are limited treatment options available for ARDS outside of last resort options such as mechanical ventilation and extracorporeal support strategies. Aim of Review: A complication of ARDS is the development of pulmonary hypertension (PH); however, the mechanisms that lead to PH in ARDS are not fully understood. In this review we summarize the known mechanisms that promote PH in ARDS. Key Scientific Concepts of Review: (1) Provide an overview or acute respiratory distress syndrome; (2) Delineate the mechanisms that contribute to the development of PH in ARDS; (3) Address the implications of PH in the setting of coronavirus disease 2019 (COVID-19)